Depersonalisation-derealisation as a transdiagnostic treatment target: a scoping review of the evidence in anxiety, depression, and psychosis - Černis, Emma; Antonović, Milan; Kamvar, Roya; Perkins, Joe; , The Transdiagnostic DPDR Project Lived Experience Advisory Panel; Chandler, Louise; Corrigan, L.; Lee, Nanette; Metz, Sara; Njoroge, Judah (Frontiers in Psychology, 2025)
IntroductionDepersonalisation and derealisation (DPDR) describe dissociative experiences involving distressing feelings of disconnection from oneself or one’s surroundings. Such experiences are common transdiagnostically across the range of mental health presentations, with evidence to suggest they may even play an active role in the development and maintenance of other mental health concerns. If substantiated, DPDR could present a plausible novel transdiagnostic treatment target. The objective of this scoping review was to therefore to synthesise the evidence-base regarding DPDR as a transdiagnostic target for the treatment of anxiety, depression, and psychosis, in order to evaluate this proposal for each.MethodsEmbase, Ovid MEDLINE, APA PsychInfo, Scopus, and PubMed were searched for empirical published research and “grey” literature addressing transdiagnostic DPDR and primary anxiety, depression, or psychotic disorders (time range: 1993 to 12th October 2023). Extracted data were summarised and provided to the Lived Experience Advisory Panel for interpretation and analysis.ResultsWe screened 3,740 records, resulting in 42 studies addressing DPDR in the context of psychosis, 28 in anxiety, and 24 in depression. The results indicate that transdiagnostic DPDR is highly likely to be a viable treatment target in psychosis, and that it may share common cognitive processes with anxiety disorders. Evidence for the feasibility of DPDR as a treatment target in depression was sparse, and thus inconclusive.DiscussionWhilst no established interventions targeting transdiagnostic DPDR were identified by this review, its findings highlight many viable options for treatment development. Given the difficulty drawing clinically meaningful conclusions from the current evidence-base, we strongly recommend that this work actively involves people with lived experience of DPDR.Systematic review registrationhttps://osf.io/ufbkn/.